1990
DOI: 10.1073/pnas.87.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Stable DNA heteroduplex formation catalyzed by the Escherichia coli RecA protein in the absence of ATP hydrolysis.

Abstract: A question remaining to be answered about RecA protein function concerns the role of ATP hydrolysis during the DNA-strand-exchange reaction. In this paper we describe the formation ofjoint molecules in the absence of ATP hydrolysis, using adenosine 5'-[r-thio]triphosphate (ATP[yS]) as nucleotide cofactor. Upon the addition of double-stranded DNA, the ATP[ySJ-RecA protein-single-stranded DNA presynaptic complexes can form homologously paired molecules that are stable after deproteinization. Formation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
214
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(231 citation statements)
references
References 23 publications
16
214
1
Order By: Relevance
“…The smooth helical backbone appears relatively unchanged. Whereas ATP-␥-S, even though is is slowly hydrolyzed, has been shown in many structural and biochemical studies with the RecA protein to be a good analog for ATP (32,33), our observations indicate that ATP-␥-S and ATP induce two different filamentous states of the hRad51 protein on ssDNA. This finding is consistent with biochemical observations suggesting that ATP-␥-S and ATP behave differently with respect to the Rad51 and RecA proteins.…”
Section: N-terminal Domain Of Rad51mentioning
confidence: 55%
“…The smooth helical backbone appears relatively unchanged. Whereas ATP-␥-S, even though is is slowly hydrolyzed, has been shown in many structural and biochemical studies with the RecA protein to be a good analog for ATP (32,33), our observations indicate that ATP-␥-S and ATP induce two different filamentous states of the hRad51 protein on ssDNA. This finding is consistent with biochemical observations suggesting that ATP-␥-S and ATP behave differently with respect to the Rad51 and RecA proteins.…”
Section: N-terminal Domain Of Rad51mentioning
confidence: 55%
“…We propose that the DNA structure with the deoxyribose-base stacking has sufficient flexibility to allow the spontaneous conformational change required for base pair switching. This flexible property would be of advantage to the process of homologous pairing, because homologous pairing occurs very quickly without exogenous energy supply such as ATP hydrolysis (59)(60)(61). The base rotation through the conversion of sugar puckers might be driven by thermodynamic molecular motions and could progress easily by using the energy provided by external heat under physiological temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Various biochemical studies indicated that homologous pairing and strand exchange can occur by using the nonhydrolyzable ATP analog, ATP␥S (60,61), or by a mutant RecA protein (RecA K72R) that exhibits Ͼ600-fold reduced level of an NTP hydrolysis (62,63). Active RecA filaments formed in the presence of both ATP and DNA exhibit an extended structure with helical pitch of Ϸ95 Å (19,(31)(32)(33), whereas in the presence of ADP or the absence of nucleotide cofactors, RecA protein formed collapsed filaments with a helical pitch of Ϸ64 Å (64-68).…”
mentioning
confidence: 99%
“…However, the initiation of DNA pairing in the presence of ATP␥S should occur in a manner similar to the more extended DNA strand exchange. As is the case for the DNA strand exchange reaction with ATP, the optimal conditions for RecA protein-promoted formation of joint molecule intermediates in the presence of ATP␥S include magnesium ion concentrations in significant excess relative to the ATP␥S that is present (30). We examined the effect of DNA overhangs on both wild-type RecA and RecA⌬C17-promoted DNA strand exchange reactions.…”
Section: Mg 2ϩ Affects Reca C Terminusthe Reca⌬c17 Deletion Mutant Rementioning
confidence: 99%